Violence and the crime drop - Ganpat, Soenita M. (European journal of criminology, 2022)
According to the Crime Survey for England and Wales, violence fell dramatically between 1995 and 2013/14. To improve understanding of the fall in violent crime, this study examines long-term crime trends in England and Wales over the past two decades, by scrutinizing the trends in (a) stranger and acquaintance violence, (b) severity of violence, (c) age groups, and (d) sexes. It draws on nationally representative, weighted data from the Crime Survey for England and Wales, and examines prevalence, incidence and crime concentration trends. The overall violence fall was driven by a decline in the victimization of young individuals and/or males perpetrated by acquaintances since 1995. Stranger and acquaintance violence followed different trajectories, with the former beginning to drop post 2003/4. Falls in both stranger and acquaintance violence incidence rates were led by a reduction in victims over time. Counting all incidents reported by the same victim (instead of capping at five incidents) significantly affects trends in stranger violence but not in acquaintance violence. In relation to the distributive justice within the crime drop, this study provides unique evidence of equitable falls in acquaintance violence but inequitable falls in stranger violence. These findings highlight the need to examine violence types separately and point to a number of areas for future research.